Increasing Incidence of Nontuberculous Mycobacteria, Taiwan, 2000–2008 - Chih-Cheng Lai; Che-Kim Tan; Chien-Hong Chou; Hsiao-Leng Hsu; Chun-Hsing Liao; Yu-Tsung Huang; Chuan-Liang Kao; Kwen-Tay Luh; Po-Ren Hsueh (Emerging Infectious Diseases, 2010)
To assess the species distribution and epidemiologic trends of nontuberculous mycobacteria, we examined isolates from patients in Taiwan. During 2000–2008, the proportion increased significantly from 32.3% to 49.8%. Associated disease incidence increased from 2.7 to 10.2 cases per 100,000 patients. Mycobacterium avium complex and M. abscessus were most frequently isolated.